Volume 9: Aesthetics and Philosophy of Art
VIII, 414 p.
Keywords: The present volume is a continuation of the series Contemporary Philosophy (International Institute of Philosophy). As with the earlier volumes in the series, the present chronicles purport to give a survey of significant trends in contemporary philosophy. This volume on Aesthetics, containing nineteen surveys, shows the variety of approaches to Aesthetics in various cultures. The close connection between aesthetics and religion and between aesthetics and ethics is emphasized in several contributions. The chronicles are as a rule written in English, French and German. In the present volume ten surveys are written in English, eight in French and one in German. The bibliographical references, with some exceptions, follow the pattern introduced in earlier volumes. The bibliographies themselves usually follow at the end of each chronicle arranged in alphabetical order. The bibliographies are selected and arranged by the authors themselves.